Endovascular repair of thoracic aortic disease with isolated left vertebral artery and unfavorable proximal landing zone using fenestrated castor stent-graft - Wang, Zhenhua; Fang, Changcun; Song, Han; Wei, Duoliang; Meng, Xiangbin; Bai, Xiao; Liu, Chunxiao; Zhao, Xin (Frontiers in Cardiovascular Medicine, 2023)
Abstract Objective: The main purpose of this study was to evaluate the safety and efficacy of Castor single-branched stent-graft combined with fenestrated technique in treatment of thoracic aortic disease (TAD) with unfavorable proximal landing area (PLZ) and isolated left vertebral artery (ILVA). Methods: From January 2018 to March 2022, 8 patients with TAD (6 patients with type B aortic dissections, 1 patient with type B intramural hematomas, and 1 patient with thoracic aortic aneurysm) underwent thoracic endovascular aortic repair with fenestrated Castor stent-graft due to the existence of ILVA and unfavorable PLZ. Demographic characteristics, surgical details, postoperative complications, follow-up and postoperative CTA imaging results were collected and analyzed. Results: The primary technical success rate was 100%. The mean operation time was 115 minutes (range, 70-180 minutes). All the left subclavian arteries (LSAs) and ILVAs of the eight patients were revascularized by fenestrated Castor stent-grafts. During the follow-up period, no deaths and complications were observed. No internal leakage, aortic rupture, retrograde type A dissection were found on computed tomography angiography. All of the LSAs and ILVAs maintained patency without stenosis. Conclusion: Castor single-branched stent-graft implantation combined with fenestration technique may be safe and feasible for TAD patients with ILVA and unfavorable PLZ.